How to make an apple pie and see the world - Priceman, Marjorie (New York : A.A. Knopf : Distributed by Random House, 1994)
Since the market is closed, the reader is led around the world to gather the ingredients for making an apple pie. Includes recipe.
Map on lining papers.
AD 590
AD 590
Accelerated Reader AR
Keywords: Pies -- Juvenile fiction; Food -- Juvenile fiction; Voyages and travels -- Juvenile fiction; Humorous fiction